Pengaruh Komitmen, Kompetensi, dan Motivasi Kerja terhadap Kinerja Guru SMK Negeri di Kota Binjai - Prihatinni Prihatinni; Elfrianto Elfrianto; Sri Nurabdiah Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to test and analyze whether there is an influence of commitment, competence and work motivation on the performance of State Vocational School Teachers in Binjai City. The method used in this study is a quantitative method. The population in this study amounted to 150 people, while the sampling technique used was the Slovin method with a total sample of 109 people. The data collection tool used was a questionnaire measured by a Liker scale. Based on the test results it can be concluded that Commitment has a positive and significant influence on Teacher Performance (H1 is accepted), Competence has a positive and significant influence on Teacher Performance (H2 is accepted), Work Motivation has a positive and significant influence on Teacher Performance (H3 is accepted), Commitment , Competence, and Work Motivation have a positive and significant effect on the performance of State Vocational School teachers in Binjai City (H4 is accepted). In conclusion, there is a positive and significant influence between commitment, competence, and work motivation on the performance of State Vocational School teachers in the city of Binjai. Keywords: commitment, competence, teacher performance, work motivation